Clinical outcomes evaluation of congenital megacolon (Hirschsprung disease) short segment type after transanal endorectal pull through at Moewardi Hospital Surakarta - Ismail, Erwin A.; Suwardi; S. A., Ida B. Budhi; Agustriani, Nunik; Sungkar, Amru; Tusarawardaya, Setya A. (International Surgery Journal, 2023)
Background: Congenital megacolon occurs in 1 in 5000 live births, with an estimated 1200 cases annually in Indonesia, predominantly affecting males. Mortality and morbidity in these patients can be reduced through improved diagnosis, neonatal care, surgical techniques, and enterocolitis management. The transanal endorectal pull through (TEPT) procedure, a minimally invasive surgery, is the common definitive treatment for congenital megacolon, performed even in neonates. However, TEPT can lead to post-operative anorectal dysfunction, necessitating assessment through fecal continence evaluation. The aims of this study is to understand of the clinical outcome congenital megacolon short segment type after TEPT procedure at Moewardi Hospital, Surakarta. Methods: The study is a cross sectional descriptive analysis in patients with congenital megacolon short segment type who have received TEPT treatment at Moewardi Hospital Surakarta from 2010 until 2022. Results: Among the patients, 18.9% exhibited normal anorectal function, 54.1% had good continence, 24.3% had moderate continence, and 2.7% experienced incontinence. Surgery age was mostly between 1 and 12 months (64.9%), with 62.2% achieving good continence. At the 1-5-year follow-up, 48.6% had good continence. Among primarily male patients (86.1%), 43.2% had good continence. Strong correlation (Pearson Chi-square score: 0.001) confirmed the relationship between age at the time of surgery and anorectal function outcomes. Conclusions: TEPT yielded favorable anorectal function outcomes in short-segment congenital megacolon patients, with surgery age significantly impacting these outcomes. This study supports the hypothesis that surgery age influences anorectal function outcomes after TEPT at Moewardi Hospital, Surakarta.